Katzung's Basic & Clinical Pharmacology - Vanderah, Todd W. (A LANGE medical book, 2024)
The most comprehensive and authoritative pharmacology text?updated with new content and USMLE-style questions. Presented in full-color and packed with hundreds of illustrations, Katzung's Basic and Clinical Pharmacology is the wide-ranging, engaging guide students have counted on for decades. To be as clinically relevant as possible, the book includes sections that specifically address the clinical choice and use of drugs in patients and the monitoring of their effects, along with case studies that introduce clinical problems. Each chapter opens with a case study, covers drug groups and prototypes, and closes with summary tables and diagrams that encapsulate important information. Updated to reflect the latest research, this sixteenth edition features a new chapter on cannabinoids, USMLE-style questions, new drug tables, and more.